FAKTOR YANG MEMPENGARUHI PEMANFAATAN PELAYANAN KESEHATAN DI WILAYAH PESISIR - Susilawati Susilawati; Dea Azzahra (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
Health service utilization is an important determinant of health, which should be of particular concern as a public health and development problem in low-income countries. The World Health Organization (WHO) also recommends the use of medical services as a basic and primary health concept for the most vulnerable and disadvantaged. The purpose of this study was to identify factors related to utilization of coastal health services. Data collection was taken from Google Scholar using the keywords: factors, related, utilization and service. Research journals were taken in 2016-2020, then reviewed again according to the inclusion and exclusion criteria applied by the authors. The results of the literature show that there are variables of knowledge, tradition, attitudes, accessibility, health personnel, income and education with the use of health services for people in coastal areas